PRINCIPLES AND METHODS OF COMPARATIVE PHRASEOLOGY - Ibodullaeva Shirina Mirzhakhon qizi (Scholar Express Journal, 2024)
Comparative phraseology is a field of study that examines the similarities and differences between phrases in different languages. This article explores the principles and methods used in comparative phraseology, including the identification of equivalent phrases, the analysis of phrase structures, and the comparison of idiomatic expressions. By understanding the underlying principles of comparative phraseology, researchers can gain insights into how languages express similar concepts in unique ways.
Keywords: Comparative phraseology; Equivalence; Idiomatic expressions